Model Potential Approach for Positronium Impact Ionization of Alkali Atoms - Ghosh, Dipali (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2018)
Positronium impact target ionization processes of alkali atoms are investigated in the frame work of model potential formalism and using the Coulomb distorted eikonal approximation. Alkali atoms are visualised as one electron species and to take the effect of the core electrons, the valence electron is assumed to move in the field of a model potential. Interesting qualitative features are noted both in the ejected electron and scattered Ps distributions in triple differential as well as double differential levels of the collision cross sections.